A study on the influence of reposition threshold on low-carbon empty container repositioning strategy under an uncertain environment - Tang, Xin; Xu, Changyan; Wang, Chuanxu; Song, Jingyao (Frontiers in Marine Science, 2023)
To enhance the cooperation among port groups, optimization of empty container reposition net has become an essential problem. In this light, our research proposed three optimization models of multi-port low-carbon empty container reposition considering threshold. Non-reposition strategy means the highest threshold, and complete-reposition strategy means the lowest threshold, threshold-reposition strategy is in the middle. Setting the input and output of empty containers as random variables, we calculated the probability of empty containers inventory in each port, and obtained the storage cost, reposition cost, lease cost and carbon emission cost of empty containers as well as the proportions of dependence on a port’s own empty containers, on other ports and on a leasing company. We used actual cases for analysis, and the results have shown that: (1) Compared with non-reposition strategy, the threshold-reposition strategy and complete-reposition strategy can reduce the port’s storage costs and lease costs of empty containers and also reduce carbon emissions. The lower the reposition threshold of empty containers between ports is, the more obvious the advantages of the threshold-reposition strategy become. (2) When the cost of storage per empty container increases, under three strategies, the total cost, storage cost, lease cost and carbon emission cost of the port will all increase. The port’s proportion of dependence on its own empty container storage will decrease, and the proportion of dependence on other ports and leasing company will both increase. The higher the reposition threshold of empty containers between ports is, the higher the total cost, storage cost, reposition cost and lease cost of ports under the threshold-reposition strategy will become. The proportion of dependence on the port’s own empty container storage under the threshold-reposition will increase, and the proportion of dependence on leasing company will decrease.